Belt Sets of the Atkarskiy Burial Ground - Aleksey Rakushin (Нижневолжский археологический вестник)
The article discusses materials of belt sets from 7 burials of the Atkarskiy burial ground located on the territory of the Saratov region. The preserved belt sets and their individual elements are kept in the collections of the Saratov and Atkarsk Museums of Local History. Among the 107 burials of the burial ground, which contained skeletal remains of 112 individuals, belts and their individual elements were traced in 11 burials. The metal parts of the belt sets were poorly preserved, since the tips of the belts and the lining made of bronze alloys were products made of a thin sheet with an impression of a matrix image, and the iron was simply heavily corroded. Non-preserved and poorly preserved belt sets are described according to field reports and publications by the authors of the excavations. Belts with an iron headset are often located on the pelvis and hips, with a bronze and bone (horn) headset laid out at the left hand of the buried. The origin of the iron headset is connected with the products of the Askiz circle. The bone tip and two belt clips from burial No. 60 turned out to be the closest to the horn Bulgarian products of the Golden Horde period. Belts with bronze buckles, clips, and overlays are very diverse in their origin and manufacturing technology, which allows us to trace both the indigenous Finno-Ugric traditions and the fashion associated with the manufacture of such products in various districts of the Mongolian Empire and the cities of the Golden Horde. Among them there are belts decorated with floral ornaments, as well as products with images of dragons and deer. The method of dating by analogy was used in the work, which made it possible to clarify the time of existence of a number of belt sets of the Atkarskiy burial ground.